SQM/COSMO Scoring Function at the DFTB3-D3H4 Level: Unique Identification of Native Protein-Ligand Poses - Pecina, Adam; Haldar, Susanta; Fanfrlík, Jindřich; Meier, René; Řezáč, Jan; Lepšík, Martin; Hobza, Pavel (Journal of chemical information and modeling, 2017)
We have recently introduced the "SQM/COSMO" scoring function which combines a semiempirical quantum mechanical description of noncovalent interactions at the PM6-D3H4X level and the COSMO implicit model of solvation. This approach outperformed standard scoring functions but faced challenges with a metalloprotein featuring a Zn(2+)···S(-) interaction. Here, we invoke SCC-DFTB3-D3H4, a higher-level SQM method, and observe improved behavior for the metalloprotein and high-quality results for the other systems. This method holds promise for diverse protein-ligand complexes including metalloproteins.
Keywords: Protein Binding; Ligands; termodynamika; vazba proteinů; Quantum Theory; kvantová teorie; Metalloproteins; ligandy; metaloproteiny; Thermodynamics